Mechanisms for axon maintenance and plasticity in motoneurons: alterations in motoneuron disease. Issue 1 (6th September 2013) - Jablonka, Sibylle; Dombert, Benjamin; Asan, Esther; Sendtner, Michael
Abstract In motoneuron disease and other neurodegenerative disorders, the loss of synapses and axon branches occurs early but is compensated by sprouting of neighboring axon terminals. Defective local axonal signaling for maintenance and dynamics of the axonal microtubule and actin cytoskeleton plays a central role in this context. The molecular mechanisms that lead to defective cytoskeleton architecture in two mouse models of motoneuron disease are summarized and discussed in this manuscript. In the progressive motor neuropathy (pmn) mouse model of motoneuron disease that is caused by a mutation in the tubulin‐specific chaperone E gene, death of motoneuron cell bodies appears as a consequence of axonal degeneration. Treatment with bcl‐2 overexpression or with glial‐derived neurotrophic factor prevents loss of motoneuron cell bodies but does not influence the course of disease. In contrast, treatment with ciliary neurotrophic factor (CNTF) significantly delays disease onset and prolongs survival of pmn mice. This difference is due to the activation of Stat‐3 via the CNTF receptor complex in axons of pmn mutant motoneurons. Most of the activated Stat‐3 protein is not transported to the nucleus to activate transcription, but interacts locally in axons with stathmin, a protein that destabilizes microtubules. This interaction plays a major role in CNTF signaling for microtubule dynamics in axons. In Smn‐deficient mice, a model of spinal muscular atrophy, defects in axonal translocation of β‐actin mRNA and possibly other mRNA species have been observed. Moreover, the regulation of local protein synthesis in response to signals from neurotrophic factors and extracellular matrix proteins is altered in motoneurons from this model of motoneuron disease. These findings indicate that local signals are important for maintenance and plasticity of axonal branches and neuromuscular endplates, and that disturbances in these signaling mechanisms could contribute to the pathophysiology of motoneuron diseases.